PENGARUH UKURAN PERUSAHAAN DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (STUDY EMPIRIS PADA PERUSAHAAN LQ45) - Anggela Desisca; Yuliana, Yuliana; Mezi Oktaliza (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to examine the effect of company size and corporate social responsibility (CSR) on firm value in LQ45 companies listed on the Indonesia Stock Exchange for the 2019–2023 period. The research method used is a quantitative approach with a purposive sampling technique, resulting in 20 companies as samples. Data were analyzed using multiple linear regression with the help of SPSS software version 26. The results show that company size and CSR simultaneously have a significant effect on firm value. Partially, both variables also show a positive and significant effect on firm value. The conclusion of this study is that the larger the company size and the higher the CSR disclosure, the higher the firm value. Keywords: Company Size, CSR, Company Value, LQ45